USE OF ELECTRONIC CONTENT IN THE TRAINING OF FUTURE PHYSICS TEACHERS - Avezova К.Ж.; Sarsenbaeva Г.М.; Kozybay А.Қ. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
This article discusses the effectiveness of the use of information and communication technologies in the educational process, use of modern innovative teaching technologies in the system of training of future specialists. The strategy of the state policy for the development of education requires a transition to digitalization technologies. In this regard, there is a need to introduce rational solutions of information and communication technologies in all areas of the economy, including education. The article presents the recommendations of domestic scientists and methodologists who studied didactics and methods for the widespread use of information and communication technologies in the educational process. One of the most effective products of information and communication technologies is the value of cognitive, informative and active components for the use of electronic content in the educational process in the process of training of future teachers. In conclusion, descriptions are given of a number of basic principles that are recommended to be guided in the development of electronic content for specific disciplines.